2007
DOI: 10.3390/s7112881
|View full text |Cite
|
Sign up to set email alerts
|

Tempo-Spatial Patterns of Land Use Changes and Urban Development in Globalizing China: A Study of Beijing

Abstract: This study examines the temporal and spatial changes in land use as a consequence of rapid urban development in the city of Beijing. Using a combination of techniques of remote sensing and GIS, the study identifies a substantial loss of plain dryland and a phenomenal expansion of urban construction land over the recent decade. Geographically, there is a clear shifting of urban construction land from the inner city to the outskirts as a consequence of suburbanization. The outward expansion of the ring-road syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(30 citation statements)
references
References 70 publications
1
27
0
Order By: Relevance
“…This is documented as mosaic of opportunities and threats to people living in peripheral villages (Aberra & King, 2005;Xie et al, 2007;Olujimi, 2009). A key challenge to the urbanisation process is the rapid conversion of large amount of prime agricultural land to urban land use as well as transformation in the livelihoods of peri-urban dwellers (Owusu & Agyei, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…This is documented as mosaic of opportunities and threats to people living in peripheral villages (Aberra & King, 2005;Xie et al, 2007;Olujimi, 2009). A key challenge to the urbanisation process is the rapid conversion of large amount of prime agricultural land to urban land use as well as transformation in the livelihoods of peri-urban dwellers (Owusu & Agyei, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Urbanization is a complex process involving rural-urban shift, urban expansion, and land use change [1][2][3][4][5][6]. The urban expansion process leads to a shortage of natural resources, a number of environmental changes and even disasters on multiple scales [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Xu et al [17] have observed that this major pattern in Nanjing has transformed the city since 1988 from expansion to infilling and leapfrogging. The sprawl of Beijing is based on urban traffic loops of concentric circles [43], while Hangzhou and Wuhan have shown the typical polycentric expansion patterns [18,44]. We could conclude that there is not one simple pattern that works to describe development and expansion in all Chinese cities.…”
Section: Literature Reviewmentioning
confidence: 96%
“…Empirical studies (e.g., [15,18,[43][44][45]) find that diverse patterns across cities are due to dissimilar geographic and economic conditions. For example, in Chengdu, geographers find that the major pattern before 2000 is expansion, but after 2000, infilling and leapfrog become the major patterns of urban growth [16].…”
Section: Literature Reviewmentioning
confidence: 99%